2017
DOI: 10.1007/s15010-016-0978-8
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of serious rhabdomyolysis during linezolid treatment

Abstract: Linezolid is an oxazolidinone antibiotic with activity against gram-positive organisms, particularly methicillin-resistant Staphylococcus aureus (MRSA). To the best of our knowledge, there are only two case reports on rhabdomyolysis in patients treated with linezolid. Here, we describe two cases of serious rhabdomyolysis: one in a patient with septic community-acquired (CA)-MRSA pneumonia and a second case in a patient with suspected catheter-related blood stream infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Our results demonstrated significant rhabdomyolysis associations (from strongest to weakest) with daptomycin, cefditoren, cefaclor, erythromycin, norfloxacin, clarithromycin, meropenem, azithromycin, cefdinir, piperacillintazobactam, trimethoprim-sulfamethoxazole, linezolid, and ciprofloxacin. Our results confirmed previously known rhabdomyolysis associations with daptomycin, macrolides, trimethoprimsulfamethoxazole, linezolid, fluoroquinolones, and cefdinir [2][3][4][5][6][7][8][9][10][11][12][13][14]. Meropenem, cefditoren, cefaclor, and piperacillin-tazobactam were found to be associated with rhabdomyolysis, which were not reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrated significant rhabdomyolysis associations (from strongest to weakest) with daptomycin, cefditoren, cefaclor, erythromycin, norfloxacin, clarithromycin, meropenem, azithromycin, cefdinir, piperacillintazobactam, trimethoprim-sulfamethoxazole, linezolid, and ciprofloxacin. Our results confirmed previously known rhabdomyolysis associations with daptomycin, macrolides, trimethoprimsulfamethoxazole, linezolid, fluoroquinolones, and cefdinir [2][3][4][5][6][7][8][9][10][11][12][13][14]. Meropenem, cefditoren, cefaclor, and piperacillin-tazobactam were found to be associated with rhabdomyolysis, which were not reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, case reports indicated that trimethoprim-sulfamethoxazole induced rhabdomyolysis occurred in both immunocompetent and immunocompromised patients [8,9]. There have been case reports linking the use of linezolid to serious cases of rhabdomyolysis [10,11]. Fluoroquinolones have also been shown to be associated with rhabdomyolysis in case reports when fluoroquinolones were used alone or in combination with statins [12,13].…”
Section: Ivyspringmentioning
confidence: 99%
“…There are two reported cases of linezolid induced rhabdomyolysis [ 5 , 8 ]. Rhabdomyolysis has been associated with drugs that inhibit mitochondrial function [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the patient’s fever recurred and he became more haemodynamically unstable, requiring escalated inotropic support. As there were reported cases of linezolid induced rhabdomyolysis, we considered linezolid as the offending agent [ 5 ]. Withdrawal of linezolid resulted in the recovery of AKI and rhabdomyolysis.…”
Section: Case Presentationmentioning
confidence: 99%
“…Rhabdomyolysis is a potentially lifethreatening disease caused by damage to muscle cells and the subsequent release of cellular components into the bloodstream (Stahl et al, 2020). Four cases of rhabdomyolysis associated with linezolid have been reported (Allison et al, 2009;Carroll et al, 2012;Lechner et al, 2017). Moreover, a FAERS-based study identified an association between linezolid and prolongation of the QT interval along with a higher incidence in TB patients (Shao et al, 2023).…”
Section: Ades At Other Soc Levelsmentioning
confidence: 99%